2009
DOI: 10.1016/j.archoralbio.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Enamel defects in extracted and exfoliated teeth from patients with Amelogenesis Imperfecta, measured using the extended enamel defects index and image analysis

Abstract: AimsTo enhance the phenotypic description and quantification of enamel defects from a North Sweden sample of extracted and exfoliated teeth originating from families with Amelogenesis Imperfecta by use of the extended enamel defects index (EDI) and image analysis to demonstrate the comparable reliability and value of the additional measurements.Methods and resultsThe sample comprised 109 deciduous and 7 permanent teeth from 32 individuals of 19 families with Amelogenesis Imperfecta in Northern Sweden. A specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
1
17
1
2
Order By: Relevance
“…In the present study, a SEM analysis revealed positive surface alterations after treatment with a CPP-ACP or CPP-ACFP paste which is in accordance with previously published results [16]. The image analysis technique permits reliable measurements and can produce detail and objective data through an assessment of a great number of variables [33]. When the influence of pastes containing CPP-ACP/CPP-ACFP and 0.05 % NaF on surface characteristics of demineralised enamel in an in vitro study was examined, significant alterations in enamel morphology have been found after treatment with both CPP-ACP and CPP-ACFP, with the CPP-ACFP having the most pronounced effect [34].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, a SEM analysis revealed positive surface alterations after treatment with a CPP-ACP or CPP-ACFP paste which is in accordance with previously published results [16]. The image analysis technique permits reliable measurements and can produce detail and objective data through an assessment of a great number of variables [33]. When the influence of pastes containing CPP-ACP/CPP-ACFP and 0.05 % NaF on surface characteristics of demineralised enamel in an in vitro study was examined, significant alterations in enamel morphology have been found after treatment with both CPP-ACP and CPP-ACFP, with the CPP-ACFP having the most pronounced effect [34].…”
Section: Discussionsupporting
confidence: 92%
“…The index is binary in nature and has a value range from 0,0,0 to 1,1,1, the former indicating no visible defect of any kind (hypoplasia, opacity or post-eruptive breakdown) is present and the latter indicating all 3 are present on the tooth surface under scrutiny. The teeth used in this study are a subset of a much larger collection of teeth for which the EDI has been determined [Smith et al, 2008].…”
Section: Edi and Image Analysismentioning
confidence: 99%
“…Os mais evidentes são as alterações na composição do esmalte dental, tanto em quantidade e qualidade (áreas hipoplásicas nas superfícies oclusais são o defeito mais frequentemente encontrado. A superfície oclusal apresenta maior degradação pós-eruptiva, enquanto que a porção incisal das superfícies vestibulares mostra maior opacidade difusa 10 …”
Section: Discussionunclassified